NS6180, a new KCa3.1 channel inhibitor prevents T‐cell activation and inflammation in a rat model of inflammatory bowel disease. (20th December 2012) - Strøbæk, D; Brown, DT; Jenkins, DP; Chen, Y‐J; Coleman, N; Ando, Y; Chiu, P; Jørgensen, S; Demnitz, J; Wulff, H; Christophersen, P
Abstract : Background and Purpose: The KCa 3.1 channel is a potential target for therapy of immune disease. We identified a compound from a new chemical class of KCa 3.1 inhibitors and assessed in vitro and in vivo inhibition of immune responses. Experimental Approach: We characterized the benzothiazinone NS6180 (4‐[[3‐(trifluoromethyl)phenyl]methyl]‐2 H ‐1, 4‐benzothiazin‐3(4 H )‐one) with respect to potency and molecular site of action on KCa 3.1 channels, selectivity towards other targets, effects on T‐cell activation as well as pharmacokinetics and inflammation control in colitis induced by 2, 4‐dinitrobenzene sulfonic acid, a rat model of inflammatory bowel disease (IBD). Key Results: NS6180 inhibited cloned human KCa 3.1 channels (IC50 = 9 nM) via T250 and V275, the same amino acid residues conferring sensitivity to triarylmethanes such as like TRAM‐34. NS6180 inhibited endogenously expressed KCa 3.1 channels in human, mouse and rat erythrocytes, with similar potencies (15–20 nM). NS6180 suppressed rat and mouse splenocyte proliferation at submicrolar concentrations and potently inhibited IL‐2 and IFN‐γ production, while exerting smaller effects on IL‐4 and TNF‐α and no effect on IL‐17 production. Antibody staining showed KCa 3.1 channels in healthy colon and strong up‐regulation in association with infiltrating immune cells after induction of colitis. Despite poor plasma exposure, NS6180 (3 and 10 mg·kg −1 b.i.d.) dampened colon inflammation and improved body weight gain as effectively as the standard IBD drug sulfasalazine (300 mg·kg −1 q.d.). Conclusions and Implications: NS6180 represents a novel class of KCa 3.1 channel inhibitors which inhibited experimental colitis, suggesting KCa 3.1 channels as targets for pharmacological control of intestinal inflammation.